MYCN Drives a Tumor Immunosuppressive Environment Which Impacts Survival in Neuroblastoma - Raieli, Salvatore; Di Renzo, Daniele; Lampis, Silvia; Amadesi, Camilla; Montemurro, Luca; Pession, Andrea; Hrelia, Patrizia; Fischer, Matthias; Tonelli, Roberto (Frontiers in Oncology, 2021)
A wide range of malignancies presents MYCN amplification (MNA) or dysregulation. MYCN is associated with poor prognosis and its over-expression leads to several dysregulations including metabolic reprogramming, mitochondria alteration and cancer stem cell phenotype. Some hints suggest that MYCN overexpression leads to cancer immune-escape. However, this relationship presents various open questions. Our work investigated in details the relationship of MYCN with the immune system, finding a correlated immune-suppressive phenotype in Neuroblastoma (NB) and different cancers where MYCN is up-regulated. We found a downregulated Th1-lymphocytes/M1-Macrophages axis and upregulated Th2-lymphocytes/M2-Macrophages in MNA NB patients. Moreover, we unveiled a complex immune network orchestrated by N-Myc and we identified 16 genes modules associated to MNA NB. We also identified a MYCN-associated immune signature that has a prognostic value in NB and recapitulates clinical features. Our signature also discriminates patients with poor survival in not-MNA NB patients where MYCN expression is not discriminative. Finally, we showed that targeted inhibition of MYCN by BGA002 (anti-MYCN antigene PNA) is able to restore NK sensibility in MYCN-expressing NB cells. Overall, our study unveils a MYCN-driven immune network in NB and shows a therapeutic option to restore sensibility to immune cells.